Cabozantinib inhibits tumor growth and metastasis of a patient-derived xenograft model of papillary renal cell carcinoma with MET mutation. Issue 11 (2nd November 2017) - Zhao, Hongjuan; Nolley, Rosalie; Chan, Andy M. W.; Rankin, Erinn B.; Peehl, Donna M.
ABSTRACT: MET plays an important role in the development and progression of papillary renal cell carcinoma (pRCC). Evaluation of efficacy of MET inhibitors against pRCC has been hampered by limited preclinical models depicting MET abnormalities. We established a new patient-derived xenograft (PDX) model of pRCC carrying an activating mutation of MET and tested the ability of cabozantinib, an inhibitor of receptor tyrosine kinases including MET, to inhibit tumor growth and metastasis. Precision-cut, thin tissue slices from a pRCC specimen obtained by nephrectomy were implanted under the renal capsule of RAG2 −/− γC −/− mice to establish first generation TSG-RCC-030. Histologic and genetic fidelity and metastatic potential of this model were characterized by immunohistochemistry, direct DNA sequencing and quantitative polymerase chain reaction (qPCR). The effect of cabozantinib on tumor growth and metastasis was evaluated. Whether measurements of circulating tumor DNA (ctDNA) by allele-specific qPCR could be used as a biomarker of tumor growth and response to therapy was determined. Subrenal and subcutaneous tumor grafts showed high take rates and metastasized to the lung. Both primary tumors and metastases expressed typical markers of pRCC and carried the same activating MET mutation as the parental tumor. Cabozantinib treatment caused striking tumor regression and inhibited lung metastasis in TSG-RCC-030. Plasma ctDNA levels correlated with tumor volume in control mice and changed in response to cabozantinib treatment. TSG-RCC-030 provides a realistic preclinical model to better understand the development and progression of pRCC with MET mutation and accelerate the development of new therapies for pRCC.